Search for black holes in multiparticle final state in proton-proton collisions at √s = 13 TEV with CMS detector / Mohammad Javad Soleimani Rahjerdi - Mohammad Javad, Soleimani Rahjerdi (2018)
Quantum gravity can become strong at a TeV energy scale in the bulk space-time in the context of large extra dimension, and could lead to microscopic black holes being produced and observed by the Large Hadron Collider (LHC) experiments. A search for black holes using a data sample corresponding to an integrated luminosity of 2:2 fb